Desempenho internacional: uma proposta de mensuração - Pereira, Alexandre (Universidade do Vale do Rio dos Sinos, 2011)
Export performance has being deeply studied on last decades, starting with Tookey´s research in the sixties. Even with a huge number of researches published about export performance there is a lack conceptual and operational consensus over the studies. Most of discrepancies mentioned over recent studies are enlightening questions about absence of operational and conceptual agreements, concentration of studies in well developed countries, small frequency of studies in emerging economies and no incidence of studies with a multicultural approach. This study has as main goal measure export performance through a scale that allows new perspectives about this matter. So, considering this Idea, concepts of performance, export performance, export performance constructs, determinants and indicators of export performance are presented. Also, a group of scales published and used during last few years are presented and analyzed. Based on previous analyze, the EXPERF scale is selected to as a base to further developments in order to minimize some of discrepancies previously mentioned. As results of this study is proposed and tested a new scale to measure export performance scale. The scale was tested statistically through SPSS and AMOS software. A survey was applied in 178 export Brazilian shoe factories. So, the main results to be considered for this study are increase of two new constructs to measure export performance named relational performance and marketing performance. Also, new indicators were added into original constructs of EXPERF scale. Both proposals presented statistic validation when the scale was tested. It was possible also validate inter-functional interaction as a export performance determinant, as well as export commitment and entry mode strategies
Keywords: Desempenho internacional; Escalas de mensuração; EXPERF; Interação; Modelagem de equações estruturais; Export performance; Measurement scales; Interaction; Strutural equations models; ACCNPQ::Ciências Sociais Aplicadas::Administração